ANALISIS KONSENTRASI KLOROFIL-A DAN SUHU PERMUKAAN LAUT MENGGUNAKAN DATA SATELIT AQUA MODIS SERTA HUBUNGANNYA DENGAN HASIL TANGKAPAN IKAN TONGKOL (Euthynnus sp.) DI SELAT MALAKA - Syafrida Siregar; Ternala Alexander Barus; Zulham Apandy Harahap (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Strait of Malacca is a strait that located between the Peninsular of Malaysia (Thailand, Malaysia, Singapore) and the island of Sumatra (Indonesia). The strait of Malacca linked between the eastern part of the Pacific Ocean and the Indian Ocean in the west. The aim of this study was to determine the variability of the concentration of chlorophyll-a and sea surface temperature (SST) as well as its relationship with the catch of tuna (Euthynnus sp.). The method used in this study is a sampling of respondents directly in the field with the interview. The factors of abundance fish Sea Surface Temperature (SST) and chlorophyll-a concentrations, to get the value of SST and chlorophyll-a concentrations using a satellite imagery Aqua’s Moderate Resolution Imaging Spectroradiometer (MODIS). The data of pelagic tuna (Euthynnus sp.) obtained from the Fishing Port Ocean in Belawan. The monthly average of SST in the Malacca Strait from Aqua MODIS satellite imagery in 2009 – 2014 range between 28,9°C– 32,29°C. The SST of Malacca Strait is following of the wind pattern that occurred in Indonesian water. The highest mackerel tuna catches occurred in the west season and the second transition. The concentration of chlorophyll-a in the research area (2009 – 2014) of Aqua MODIS satellite imagery in (2009 – 2014) ranged between 0,59 – 1,89 mg/m3. The west season is the most dominating of the chlorophyll-a concentration around 1,89 mg/m3. The relationship between SPL and the concentration of the chlorophyll-a by catch tuna showed the negative correlation. In the west and the first transition season, tuna fish has a high correlation to chlorophyll-a and low SST.Keywords : Malacca Strait, Aqua MODIS,Wind, Chlorophyll and Sea Surface Temperature, and Mackarel Tuna.